2021
DOI: 10.1097/ccm.0000000000005009
|View full text |Cite
|
Sign up to set email alerts
|

Exhalation Spreading During Nasal High-Flow Therapy at Different Flow Rates

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
5
0
2
Order By: Relevance
“…22 Indirect technologies used to evaluate the aerosol transmission risk include aerosol particle sizers, smoke light detection, schlieren imaging, and laser light scattering. [23][24][25][26][27][28][29] The latter 3 use imaging to visualize the trajectory of aerosol movement and do not measure aerosol particle size or concentrations. 13,29 Smoke light detection uses externally introduced particles to visualize the exhaled gas from the manikin, and thus it only measures aerosol dispersion potential.…”
Section: Methods To Evaluate Transmission Risk Of Respiratory Virusesmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Indirect technologies used to evaluate the aerosol transmission risk include aerosol particle sizers, smoke light detection, schlieren imaging, and laser light scattering. [23][24][25][26][27][28][29] The latter 3 use imaging to visualize the trajectory of aerosol movement and do not measure aerosol particle size or concentrations. 13,29 Smoke light detection uses externally introduced particles to visualize the exhaled gas from the manikin, and thus it only measures aerosol dispersion potential.…”
Section: Methods To Evaluate Transmission Risk Of Respiratory Virusesmentioning
confidence: 99%
“…25 Interestingly, Dellweg and colleagues evaluated exhaled emission during HFNC at 60 L/min flow on a single healthy subject using a schlieren optical system. 26 The investigators reported that HFNC increased exhaled air dispersion distance compared with baseline. The maximal dispersal distances while normally breathing room air, HFNC at flows of 20 L/min, 40 L/min, and 60 L/min were 0.99 m, 2.18 m, 2.92 m, and 4.10 m, respectively.…”
Section: Oxygen Devices Including High-flow Nasal Cannulamentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case of no mask, the exhaled jet often exceeded the mirror visualization field. In such cases, an extrapolation of the spreading distances outside the mirror area can be done using the reduction of the expired air velocity [ 32 ]. However, in the present study, this was not possible due to the constant physical movement of the subjects and the thermal plume from the subjects’ lower bodies, which made the wavefront of the expired air often indistinguishable in the schlieren recordings.…”
Section: Resultsmentioning
confidence: 99%
“…The latter has been utilized in this study due to the flexibility and high resolution of this approach that provides two-dimensional visualizations of the flow field with virtually no disturbance to the flow. Therefore, this visualization method has been frequently used in recent literature to evaluate indoor air quality topics, such as the spread of air from face masks [ 31 ], from nasal high-flow therapy [ 32 ], from music instruments [ 33 ], and ventilation strategies [ 34 ]. Detailed information about the utilized schlieren imaging system is presented in Section 2.2 .…”
Section: Introductionmentioning
confidence: 99%